A paucity of liver disease in Canadian Inuit with chronic hepatitis B virus, subgenotype B6 infection. Issue 12 (29th May 2013) - Minuk, G. Y.; MacRury, S.; Uhanova, J.; Caouette, S.; Coleman, N.; Cummings, K.; Larke, B.; Vardy, L.; Triet Huyn, C.; Osiowy, C.
Summary: Clinical observations suggest that chronic hepatitis B virus (HBV) infections in the Canadian Inuit are less often associated with serious adverse outcomes than has been described in other HBV‐infected patient populations. The aim of this study was to document the clinical and biochemical features, liver‐related morbidity and all‐cause mortality in Canadian Inuit with chronic HBV infections. Administrative databases were reviewed for individuals identified as hepatitis B surface antigen (HBsAg) positive during a 1983–85 seroepidemiological survey of viral hepatitis in Baffin Island, Canada. An equal number of age‐ and gender‐matched HBsAg‐negative individuals from the same communities served as controls. Baseline HBV viral loads, genotypes and specific mutations were compared in HBsAg‐positive survivors and nonsurvivors. A subset of surviving HBsAg‐positive carriers were reassessed 25–30 years following their initial diagnosis for evidence of advanced liver disease and changes to their serological/virological findings. One hundred and forty four HBsAg‐positive individuals were identified. All were Canadian Inuit. The mean age at diagnosis was 38 ± 17 years and 69 (61%) were male. Median follow‐up was 23 years (range: 2–28 years). Viral quantitation from stored sera could be performed in 70 infected individuals. The median viral load was 4.3 log 10 IU/ml (range: 2.3–8.8 log 10 IU/ml), and all were genotype B, subgenotype B6. Liver biochemistry, morbidity and all‐cause mortality rates were similar in HBsAg‐positive carriers and controls. Following multivariate analyses, only age at diagnosis predicted mortality in HBsAg carriers. In a subset of 30 HBsAg‐positive survivors who underwent follow‐up assessments, clinical, biochemical and radiological examinations of the liver were essentially normal. 23/30 (77%) remained HBsAg positive and 17/19 (90%) HBV‐DNA positive. The genotype and prevalence of genomic mutations in this cohort remained largely unchanged, but quantifiable viral loads were significantly lower ( P < 0.003). The results of this study suggest that chronic HBV infections in the Canadian Inuit are infrequently associated with serious adverse outcomes. Whether this finding reflects unique features of the host, presence or absence of external factors that influence the course of HBV and/or intrinsic properties of the HBV B6 subgenotype remains to be determined.